The Small World of Russian Studies in Gender Relations: An Interview with Sarah Ashwin - Sarah Ashwin (Journal of Economic Sociology, 2014)
Sarah Ashwin was interviewed by Tatiana Karabchuk, Associate Professor at the National Research University Higher School of Economics in Moscow. The conversation took place during the international conference “Embeddedness and Beyond: Do Sociological Theories Meet Economic Realities?” (Moscow, 25–28 October 2012), at which Prof. Ashwin co-chaired the mini-conference “Gender and Work Transformation” (with Prof. Roberto Fernandez of MIT). Prof. Ashwin described her background and professional trajectory, and explained how her research interest in Russia, specifically in Russian workers’ movements, developed. Prof. Ashwin shared her early impressions of Russia during the 1990’s and described her time working in Kemerovo, the administrative center of Kemerovo Oblast located in the major coal mining region of the Kuznetsk Basin in Russia. It was there she collected empirical data for her PhD dissertation on mineworkers and trade unions during the economic transition under Boris Yeltsin. Additionally, Prof. Ashwin devoted several comments to her current research interests which cover feminist movements and gender relations in Russia. Finally, Prof. Ashwin referred to several scholars working on gender relations, within and outside of the Russian context, and made some helpful reading recommendations for newcomers to this field of study.